In-situ synthesis method of MoS2 / rGO with crystal / amorphous heterogeneous interface and application of MoS2 / rGO

The in-situ synthesis method for forming MoS2/rGO electrode materials with crystalline/amorphous heterojunctions on graphene oxide solves the problem of complex preparation steps in existing MoS2-based heterojunctions and improves the electrochemical performance of sodium-ion batteries.

CN119263352APending Publication Date: 2025-01-07HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411519100.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing MoS2-based heterojunctions are all crystalline/crystalline structures, with complex preparation steps and cumbersome post-processing, resulting in poor conductivity and slow kinetics of the electrode materials in sodium-ion batteries.

Method used

An in-situ synthesis method was adopted, in which molybdenum source and sulfur source were dissolved in an alcohol dispersion of graphene oxide, and amorphous MoS2/rGO was generated through solvothermal reaction. Subsequently, annealing was carried out under gas protection to form a crystalline/amorphous heterostructure interface.

Benefits of technology

This study achieved a tight bond between MoS2/rGO electrode materials, improving ion transport efficiency, reducing charge transfer impedance, and enhancing the charge-discharge specific capacity and charge transfer performance of sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263352A_ABST
    Figure CN119263352A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ synthesis method of MoS2 / rGO with a crystal / amorphous heterogeneous interface and application of the MoS2 / rGO. The invention belongs to the field of electrode materials. The invention aims to solve the technical problems that most of the existing MoS2-based heterojunctions are crystal / crystal structures, and experimental steps and post-treatment methods are complicated. The method comprises the following steps: dissolving a molybdenum source and a sulfur source in an alcohol dispersion liquid of graphene oxide in sequence, then transferring into a hydrothermal kettle to carry out solvothermal reaction, removing by-products after the reaction is finished, and then carrying out freezing and vacuum freeze drying to obtain amorphous MoS2 / rGO; the preparation method comprises the following steps: performing primary grinding on amorphous MoS2 / rGO, performing annealing under gas protection, and performing grinding again after annealing to obtain MoS2 / rGO with a crystal / amorphous heterogeneous interface. As an electrode material, the product provided by the invention can effectively improve the ion transmission efficiency and reduce the charge transfer impedance. The method can be applied to the fields of zinc ion batteries, magnesium ion batteries and sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrode materials, and in particular relates to an in-situ synthesis method of MoS2 / rGO with a crystalline / amorphous heterogeneous interface and application thereof. Background Art

[0002] The development of new energy vehicles has significantly increased the demand for batteries, and it is very important to develop low-cost energy storage technology. Sodium resources have the advantages of wide abundance, large reserves, and environmental friendliness. Therefore, sodium-ion batteries are considered to be one of the important strategies to solve the scarcity and high cost of lithium resources. Electrode materials are one of the main components of sodium-ion batteries. Designing and synthesizing high-performance, low-cost, and environmentally friendly electrode materials to meet the requirements of high energy density and long cycle life is crucial to improving the electrochemical performance of sodium-ion batteries.

[0003] At present, the electrode materials of sodium-ion batteries are mainly crystalline materials, including carbon-based (such as graphite and carbon nanotubes, etc.), alloy-based (Sn and Sb, etc.) and metal compound-based (MoS2 and SnO2, etc.), etc. However, the inherent disadvantages of crystalline materials, including few active sites and slow redox kinetics, have hindered the development of sodium-ion batteries. In recent years, amorphous materials have attracted people's attention due to their abundant active sites and accelerated reaction kinetics. They have begun to be used as electrode materials in zinc-ion batteries, magnesium-ion batteries, etc., and various preparation methods of amorphous materials have been gradually developed, including electrodeposition, electrospinning, etc., but these methods have problems such as complex preparation process and the need for additional post-processing. Coupling crystalline and amorphous materials to construct a "crystalline / amorphous" heterojunction has become one of the effective methods to solve the problems of poor conductivity of electrode materials and slow kinetics.

[0004] Existing preparation methods for constructing "crystalline / amorphous" heterojunctions are mainly multi-step strategies, including hydrothermal-nitridation-electrodeposition, hydrothermal-calcination-solvothermal and hydrothermal-calcination-hydrothermal again, etc. However, these non-in-situ preparation strategies have problems such as large investment in time and money costs, complex processes, cumbersome by-product removal steps, and insufficient bonding between the substrate and the active material. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problems that the existing MoS2-based heterojunctions are all "crystal / crystal" structures and there are complicated experimental steps and post-processing methods, and to provide an in-situ synthesis method of MoS2 / rGO with a crystalline / amorphous heterointerface and its application.

[0006] One of the objects of the present invention is to provide an in-situ synthesis method of MoS2 / rGO with a crystalline / amorphous heterointerface, the method being carried out according to the following steps:

[0007] S1: dissolving the molybdenum source and the sulfur source in the alcohol dispersion of graphene oxide successively, and then transferring to a hydrothermal reactor for solvothermal reaction. After the reaction is completed, the by-products are removed, and then first frozen, and then vacuum freeze-dried to obtain amorphous MoS2 / rGO;

[0008] S2: After the amorphous MoS2 / rGO is initially ground, it is annealed under gas protection, and then ground again after annealing to obtain MoS2 / rGO with a crystalline / amorphous heterointerface.

[0009] It is further defined that the molybdenum source in S1 is MoO3, Na2MoO4·2H2O or (NH)6Mo7O 24 ·4H2O.

[0010] It is further defined that the sulfur source in S1 is (NH2)2SC or sulfur.

[0011] It is further defined that the alcohol in the alcohol dispersion of graphene oxide in S1 is ethylene glycol or methanol.

[0012] It is further defined that the molybdenum source and the sulfur source in S1 are dissolved in the alcohol dispersion of graphene oxide by magnetic stirring at 40-70° C. and 500-1200 rpm, and the sulfur source is added after the molybdenum source is completely dissolved.

[0013] It is further defined that the alcohol dispersion of graphene oxide in S1 is subjected to low-temperature ultrasonic treatment before use, with an ultrasonic frequency of 25 to 50 kHz, a power of 300 to 600 W, a temperature of 0 to 30° C., and a time of 0.5 to 1 h.

[0014] It is further defined that the concentration of the alcohol dispersion of graphene oxide in S1 is 1 to 4 mg / mL.

[0015] It is further defined that the ratio of the alcohol dispersion of graphene oxide to the molybdenum source and the sulfur source in S1 is 50 mL: (0.2-2) mmol: 10 mmol.

[0016] It is further defined that the solvent thermal reaction temperature in S1 is 160-200°C and the time is 20-24h.

[0017] It is further defined that in S1, by-products are removed by adding aqueous ammonia.

[0018] It is further defined that the freezing temperature in S1 is -30°C to -196°C, and the time is 24 to 72 hours.

[0019] It is further defined that the gas in S2 is an inert gas or a reducing gas.

[0020] It is further defined that the annealing temperature in S2 is 700-900°C, the time is 1-3h, and the heating rate is 5-30°C / min.

[0021] The second object of the present invention is to provide a MoS2 / rGO having a crystalline / amorphous heterointerface prepared by the above method, wherein nanocrystalline MoS2 is in-situ grown on an amorphous matrix MoS2 / rGO.

[0022] The third object of the present invention is to provide a MoS2 / rGO with a crystalline / amorphous heterointerface prepared by the above method as an electrode material for use in zinc ion batteries, magnesium ion batteries, and sodium ion batteries.

[0023] A fourth object of the present invention is to provide an electrode, wherein the electrode uses the above-mentioned MoS2 / rGO with a crystalline / amorphous heterointerface as an active component.

[0024] A fifth object of the present invention is to provide a sodium ion button battery, wherein the battery uses the above-mentioned electrode as a working electrode.

[0025] Compared with the prior art, the present invention has the following significant effects:

[0026] (1) The present invention uses graphene as a conductive substrate to form a non-crystalline MoS2 / rGO by compounding it with MoS2. The in-situ construction of a "crystalline / amorphous" heterojunction structure in amorphous MoS2 / rGO can not only combine the advantages of crystalline materials and amorphous materials, but also regulate the density of active sites and promote the transport kinetics of sodium (magnesium or zinc) ions. This is expected to increase the charge and discharge capacity of sodium (magnesium or zinc) ion batteries and reduce the charge transfer impedance. It also provides ideas for solving the problems of few crystalline active sites and difficult preparation of amorphous materials.

[0027] (2) The present invention uses an annealing method to achieve in-situ synthesis of nanocrystalline phase structure on an amorphous substrate, which not only achieves a close combination of the conductive substrate (rGO) and the active material (MoS2), improves the ion transmission efficiency, and effectively reduces the charge transfer impedance, but also effectively avoids the agglomeration of nanomaterials, ensures their uniform dispersion, and achieves maximum retention of the original structure. This is expected to provide new insights into the development of electrode materials based on the synthesis and design of "crystal / amorphous" heterojunction structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The macroscopic morphology of MoS2 / rGO-0 prepared in Comparative Example 1;

[0029] Figure 2 This is the microscopic morphology of MoS2 / rGO-0 prepared in Comparative Example 1;

[0030] Figure 3 The macroscopic morphology of MoS2 / rGO-1 prepared in Example 1;

[0031] Figure 4This is a microscopic morphology of MoS2 / rGO-1 prepared in Example 1;

[0032] Figure 5 The macroscopic morphology of MoS2 / rGO-10 prepared in Comparative Example 2;

[0033] Figure 6 This is the microscopic morphology of MoS2 / rGO-10 prepared in Comparative Example 2;

[0034] Figure 7 XRD spectra of MoS2 / rGO-0, MoS2 / rGO-1 and MoS2 / rGO-10 prepared in Example 1 and Comparative Examples 1-2;

[0035] Figure 8 HRTEM and SAED spectra of MoS2 / rGO-0 prepared for Comparative Example 1;

[0036] Fig. 9 HRTEM and SAED spectra of MoS2 / rGO-1 prepared in Example 1;

[0037] Fig.10 HRTEM and SAED spectra of MoS2 / rGO-10 prepared in Comparative Example 2;

[0038] Fig.11 The discharge specific capacity spectra of MoS2 / rGO-0, MoS2 / rGO-1 and MoS2 / rGO-10 prepared in Example 1 and Comparative Examples 1-2 at a current density of 0.1-2 A / g;

[0039] Fig.12 These are the AC impedance spectra of MoS2 / rGO-0, MoS2 / rGO-1 and MoS2 / rGO-10 prepared in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0042] Example 1: The in-situ synthesis method of MoS2 / rGO with a crystalline / amorphous heterogeneous interface of this example is carried out by the following steps:

[0043] (1) A 2 mg / mL graphene oxide ethylene glycol dispersion was subjected to low temperature ultrasonic treatment at 25 kHz, a power of 300 W, and a temperature of 25° C. for 0.5 h to obtain a uniform and stable 2 mg / mL graphene oxide ethylene glycol dispersion.

[0044] (2) First, 0.5 mmol of ammonium molybdate ((NH)6Mo7O 24 ·4H2O) was added to 50 mL of 2 mg / mL graphene oxide dispersion in ethylene glycol and stirred in a 50 °C water bath at 800 rpm for 2 h. 24 ·4H2O is completely dissolved, then add 10mmol thiourea ((NH2)2SC), keep the water bath temperature and speed unchanged, and continue magnetic stirring for 1h. First add (NH)6Mo7O 24 The purpose of adding (NH)2SC to 4H2O is to reduce the generation of MoO3 during the solvothermal process.

[0045] (3) The ethylene glycol dispersion of graphene oxide in which ammonium molybdate and thiourea are completely dissolved is transferred to the inner lining of a polytetrafluoroethylene hydrothermal autoclave and sealed, and placed horizontally in a forced air drying oven for solvent thermal reaction at 160°C for 24 hours. During the reaction, graphene oxide (GO) is reduced to reduced graphene oxide (rGO). The generated rGO is used as a substrate, and MoS2 obtained by the reaction of the sulfur source and the molybdenum source is evenly spread on the rGO, thereby finally generating the product amorphous MoS2 / rGO.

[0046] (4) After the hydrothermal kettle cools to room temperature, open the hydrothermal kettle and transfer the gray-black precipitate to a clean container, add 25% ammonia water, and let it stand for 10 hours. The addition of ammonia water can react with MoO3 to generate (NH4)2MoO4 without generating other impurities. The (NH4)2MoO4 generated when transferring the precipitate can be retained in the solution, thereby achieving the purpose of completely removing the byproduct MoO3 in the solvent thermal process. Transfer the precipitate to a clean container again, wash it with anhydrous ethanol 4 times, and then wash it with deionized water 4 times. Soaking in ammonia water and then washing with alcohol and water can remove MoO3 without introducing other impurities. Multiple alcohol washing and water washing can also completely remove residual ammonia water. The product is then placed at -196℃ and frozen for 72 hours, and then placed in a vacuum freeze dryer and freeze-dried at a vacuum degree of 1Pa for 72 hours to form a dry powder sample.

[0047] (5) The amorphous MoS2 / rGO was placed in an agate mortar and ground at room temperature until there was no obvious granularity and the particle size was uniform. Then 2.0 g of the ground amorphous MoS2 / rGO was weighed and spread flat in a square crucible, placed in a tube furnace, heated and kept warm in a H2 atmosphere, with a heating rate of 10°C / min, a holding temperature of 800°C, and a holding time of 1h. Finally, the furnace was cooled, and Ar was turned off after cooling to room temperature to obtain a MoS2 / rGO electrode material with a "crystalline / amorphous" heterojunction structure, which was recorded as MoS2 / rGO-1. The annealed MoS2 / rGO-1 was placed in an agate mortar and ground until there were no agglomerated particles and the particle diameter was less than 500μm observed under an electron microscope. The purpose of H2 atmosphere is to prevent MoS2 from oxidizing during the complete annealing process. The purpose of weighing 2.0g of amorphous MoS2 / rGO with a large mass is that MoS2 will volatilize at high temperature. The large mass of amorphous MoS2 / rGO samples can ensure that the quality of active materials in MoS2 / rGO-1 is sufficient when assembling button batteries. If the annealing time is too long, a large number of Mo and S atoms that were originally arranged in a disorderly manner will be rearranged to eventually form crystals. The reason why MoS2 / rGO-1 that has been fully annealed and cooled to room temperature is ground again is that due to the rearrangement of some disordered atoms during the complete annealing process, material defects are reduced, resulting in partial agglomeration of the sample. The uniformity of the sample particle size has a greater impact on the electrochemical performance of sodium ion batteries.

[0048] Comparative Example 1:

[0049] The difference between this comparative example and Example 1 is that no annealing is performed, that is, step (5) is not performed after step (4). The other steps and parameters are the same as those in Example 1, and the obtained product is recorded as MoS2 / rGO-0.

[0050] Comparative Example 2:

[0051] The difference between this comparative example and Example 1 is that the annealing time in step (5) is 10 h. The other steps and parameters are the same as those in Example 1, and the obtained product is recorded as MoS2 / rGO-10.

[0052] Application examples:

[0053] The electrode materials obtained in Example 1 and Comparative Examples 1-2 were respectively applied to sodium ion button batteries, and the specific process was as follows:

[0054] Using metallic sodium as the counter electrode, the electrode materials obtained in Example 1 and Comparative Examples 1-2 as the working electrode, the electrolyte 1.0M NaCIO4 dissolved in EC:DEC=1:1 (Vol%)+5%FEC, and the separator GF / A, a Na||MoS2 / rGO 2032 button cell was assembled in a glove box filled with Ar. After the battery is assembled, it needs to be placed horizontally at room temperature for 24 hours to allow the electrolyte to fully infiltrate the active material.

[0055] Effect example:

[0056] (1) The macroscopic and microscopic morphologies of MoS2 / rGO-1 obtained in Example 1 and MoS2 / rGO-0 and MoS2 / rGO-10 obtained in Comparative Examples 1-2 were observed, and the results were as follows: Figures 1 to 6 As shown. The macroscopic morphology of MoS2 / rGO-0 is gray-black cylindrical, indicating the successful preparation of the three-dimensional skeleton of reduced graphene oxide. Its microscopic morphology is thin-layered, with fewer layers, smooth surface, and a small amount of wrinkles ( Figure 2 The red circle). After 1h annealing, the color of MoS2 / rGO-1 did not change significantly, but it was gray-black, but small block particles began to appear, indicating that annealing time is one of the key factors affecting the morphology of electrode materials. Its microscopic morphology changed slightly, and the overall structure was still thin-layered. This may be attributed to the fact that the in-situ synthesized "crystal / amorphous" heterojunction can maintain the original amorphous MoS2 / rGO microscopic morphology to the greatest extent. However, the number of MoS2 / rGO-1 layers increased compared to MoS2 / rGO-0 ( Figure 4 The dotted line of the same color in the red circle is 1 layer, about 4 layers), which may be attributed to the fact that the complete annealing treatment of 1h is not enough to rearrange all the Mo, S, and C atoms in the amorphous MoS2 / rGO, but the regular arrangement of some atoms has appeared, resulting in the stacking of a small amount of MoS2 sheets. After 10h annealing, the color of MoS2 / rGO-10 is still gray-black, which is attributed to the fact that the treatment with different annealing times did not cause oxidation or deterioration of the electrode material, and the quality of the electrode material remained good. However, compared with MoS2 / rGO-0 and MoS2 / rGO-1, MoS2 / rGO-10 showed obvious agglomeration, and a large number of MoS2 particles of different sizes appeared in its microstructure. This may be attributed to the sufficiently long annealing time (10h) that caused the MoS2 / rGO-10 electrode material to recrystallize. The Mo, S, and C atoms have all been rearranged, and MoS2 / rGO-10 has completed the transformation from amorphous to partially crystallized and then to completely crystallized, which ultimately led to the appearance of a large number of MoS2 particles of different sizes in the MoS2 / rGO-10 electrode material ( Figure 6 red circle).

[0057] (2) X-ray diffraction test (XRD) was performed on MoS2 / rGO-1 obtained in Example 1 and MoS2 / rGO-0 and MoS2 / rGO-10 obtained in Comparative Examples 1-2. The results are as follows: Figure 7 As shown. MoS2 / rGO-0h has no obvious diffraction peaks, and the whole is almost a straight line, which means that the product MoS2 / rGO-0 is amorphous. Example 1 MoS2 / rGO-1 has a sharp peak, which corresponds to the characteristic peaks of crystalline MoS2 and carbon materials, representing the in-situ synthesis of crystalline MoS2 in the product MoS2 / rGO-1, indicating that annealing for 1h causes the amorphous product to begin to partially crystallize, which is consistent with the SEM analysis. When the annealing time reaches 10h, the product MoS2 / rGO-10 has a more obvious peak and corresponds to multiple characteristic crystal planes of crystalline MoS2, indicating that the complete annealing treatment of 10h makes the product completely crystallized. In addition, the (002) crystal plane representing the interlayer spacing of crystalline MoS2 is located at 14.3°. Compared with MoS2 / rGO-10, the peak angle of MoS2 / rGO-1 electrode material is further to the left (in the red circle), indicating that the interlayer spacing of MoS2 / rGO-1 electrode material is larger. This may be attributed to the fact that the shorter annealing time is not enough to completely crystallize MoS2. There are still many structural defects caused by amorphous MoS2 in MoS2 / rGO-1 electrode material, while MoS2 / rGO-10 electrode material has been completely crystallized with very few defects, resulting in a larger interlayer spacing of MoS2 / rGO-1, which also proves the existence of "crystalline / amorphous" heterojunction in MoS2 / rGO-1 electrode material. For sodium-ion batteries, a larger interlayer spacing is beneficial to Na + of embedding and extraction.

[0058] (3) MoS2 / rGO-1 obtained in Example 1 and MoS2 / rGO-0 and MoS2 / rGO-10 obtained in Comparative Examples 1-2 were subjected to transmission electron microscopy (TEM) analysis. The results are as follows: Figure 8 , 9 , 10. The SAED of MoS2 / rGO-0 shows diffuse diffraction rings typical of amorphous materials, and the HRTEM shows chaotic distribution of Mo and S atoms ( Figure 8 The red circle shows that the MoS2 / rGO-0 electrode material is all amorphous. The HRTEM of MoS2 / rGO-1 shows a chaotic atomic arrangement ( Fig. 9 The amorphous phase and orderly arrangement of atoms (outside the white circle) Fig. 9The crystal phase (in the white circle) is about 5.136nm long and has a lattice spacing of 0.281nm, which is consistent with the lattice spacing of molybdenum disulfide (100), indicating the successful preparation of nanocrystalline MoS2. In addition, selected area diffraction was performed on different regions of MoS2 / rGO-1. The results showed that the SAED of the crystalline phase region showed clearer diffraction rings, corresponding to the (002) and (100) crystal planes of crystalline MoS2, respectively, while the SAED of the amorphous phase region showed diffuse diffraction rings, proving that after 1h annealing, nanocrystalline MoS2 was in situ generated in the amorphous phase region, and the "crystalline / amorphous" heterojunction structure was successfully synthesized. After 10 hours of annealing, the SAED of MoS2 / rGO-10 showed clear diffraction rings, corresponding to the (002), (100) and (103) crystal planes of crystalline MoS2, and its HRTEM showed regularly arranged lattice fringes, proving that when the annealing time reached 10 hours, the MoS2 / rGO-10 electrode material was completely crystallized.

[0059] (4) The rate performance tests were performed on the button cells assembled with Na||MoS2 / rGO-1, Na||MoS2 / rGO-0 and Na||MoS2 / rGO-10 from MoS2 / rGO-1 obtained in Example 1 and MoS2 / rGO-0 and MoS2 / rGO-10 obtained in Comparative Examples 1-2, respectively. The results are shown in FIG. Fig.11 As shown. At current densities of 0.1, 0.2, 0.5, 1, and 2 A / g, the average discharge specific capacity of Na||MoS2 / rGO-1 in Example 1 is 407.02, 379.54, 312.64, 211.82, and 87.65 mAh / g, respectively, showing a high discharge specific capacity, while the average discharge specific capacity of Na||MoS2 / rGO-0 and Na||MoS2 / rGO-10 in Comparative Examples 1-2 is much lower than that of Na||MoS2 / rGO-1. When returning to 0.1 A / g, the capacity retention rate of Na||MoS2 / rGO-1 reaches 98.94%, with excellent reversibility, which is attributed to the "crystalline / amorphous" heterojunction structure in MoS2 / rGO-1, which provides more active sites, promotes electron transfer, shortens the ion / electron diffusion path, and significantly enhances the reaction kinetics. Secondly, the larger interlayer spacing in MoS2 / rGO-1 is conducive to Na + The embedding and extraction of Na||MoS2 / rGO-1 ultimately achieves excellent rate performance. In addition, the particle size of the electrode material will also affect the electrochemical performance. MoS2 / rGO-10 contains a large number of MoS2 particles with larger particle sizes and uneven distribution, which ultimately leads to the poor rate performance of Na||MoS2 / rGO-10.

[0060] (5) Electrochemical impedance spectroscopy (EIS) tests were performed on the MoS2 / rGO-1 obtained in Example 1 and the MoS2 / rGO-10h assembled Na||MoS2 / rGO-1 and Na||MoS2 / rGO-10h button cells obtained in Comparative Examples 1-2 to study the effect of the "crystalline / amorphous" heterojunction on the electrode ion diffusion kinetics. The results are shown in Figure 5. Fig.12 As shown. The three curves have similar characteristics, all of which are composed of a semicircle in the high-frequency region and a slash in the low-frequency region. The intersection of the semicircle in the high-frequency region and the coordinate axis is the size of the charge transfer impedance (Rct), and the slash represents the Warburg impedance (Zw) of the electrode. The semicircle radius of the MoS2 / rGO-1 electrode curve is the smallest. It is calculated that the Rct of the MoS2 / rGO-1 electrode is 590.1Ω, while the Rct of MoS2 / rGO-0 and MoS2 / rGO-10 are 852.66 and 896.1Ω, respectively. In addition, the MoS2 / rGO-1 electrode has a steeper slash, which means that MoS2 / rGO-1 has faster ion transfer kinetics. This is because compared to crystalline MoS2, the in-situ synthesized "crystalline / amorphous" heterojunction structure can be tightly combined with the conductive substrate, while providing additional charge transfer driving force, thereby effectively reducing the charge transfer impedance of the battery.

[0061] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An in-situ synthesis method of MoS2 / rGO with a crystalline / amorphous heterogeneous interface, characterized in that: The method: S1: dissolving the molybdenum source and the sulfur source in the alcohol dispersion of graphene oxide successively, and then transferring to a hydrothermal reactor for solvothermal reaction. After the reaction is completed, the by-products are removed, and then first frozen, and then vacuum freeze-dried to obtain amorphous MoS2 / rGO; S2: After the amorphous MoS2 / rGO is initially ground, it is annealed under gas protection, and then ground again after annealing to obtain MoS2 / rGO with a crystalline / amorphous heterointerface.

2. The method according to claim 1, characterized in that The molybdenum source in S1 is MoO3, Na2MoO4·2H2O or (NH)6Mo7O 24 4H2O, the sulfur source is (NH2)2SC or sulfur, and the alcohol in the alcohol dispersion of graphene oxide is ethylene glycol or methanol.

3. The method according to claim 1, characterized in that The molybdenum source and sulfur source in S1 are dissolved in the alcohol dispersion of graphene oxide by magnetic stirring at 40-70°C and 500-1200rpm. The sulfur source is added after the molybdenum source is completely dissolved. The alcohol dispersion of graphene oxide is subjected to low-temperature ultrasonic treatment before use, with an ultrasonic frequency of 25-50kHZ, a power of 300-600W, a temperature of 0-30°C, and a time of 0.5-1h.

4. The method according to claim 1, characterized in that: The concentration of the alcohol dispersion of graphene oxide in S1 is 1-4 mg / mL, and the ratio of the alcohol dispersion of graphene oxide to the molybdenum source and the sulfur source is 50 mL: (0.2-2) mmol: 10 mmol.

5. The method according to claim 1, characterized in that The solvent thermal reaction temperature in S1 is 160-200°C, the time is 20-24h, the by-products are removed by adding ammonia water, and the freezing temperature is -30°C to -196°C, and the time is 24-72h.

6. The method according to claim 1, characterized in that In S2, the annealing temperature is 700-900°C, the time is 1-3h, and the heating rate is 5-30°C / min.

7. MoS2 / rGO having a crystalline / amorphous heterointerface prepared by the method according to any one of claims 1 to 6, characterized in that: Nanocrystalline MoS2 was in situ grown on the amorphous matrix MoS2 / rGO.

8. Use of the MoS2 / rGO having a crystalline / amorphous heterointerface as claimed in claim 7 as an electrode material in zinc ion batteries, magnesium ion batteries and sodium ion batteries.

9. An electrode, characterized in that: The electrode uses the MoS2 / rGO with a crystalline / amorphous heterointerface as described in claim 7 as an active component.

10. A sodium ion button battery, characterized in that: The battery uses the electrode according to claim 9 as a working electrode.